MINIMUM INHIBITORY CONCENTRATION OF WHITE GINGER AND CHLORHEXIDINE GLUCONATE ON ACRYLIC PLATES TOWARD Candida albicans - Debby Saputera; Gusti Aulia Nalar; Lia Yulia Budiarti (FKG Unlam, 2017)
ABSTRACTBackground: Acrylic resin-based dentures are commonly used nowadays. The hygiene of denture base can be maintained by soaking the denture base into 0.2% chlorhexidine gluconate. Unhygienic denture base can lead to denture stomatitis. Flora accumulation, such as Candida albicans, may occur. White ginger is active towards Candida albicans, with antifungal properties due to its phenol compound. Aim: This study aims to determine the Minimum Inhibitory Concentration value (MIC) of the ethanol extract of white ginger towards Candida albicans growth in heat cured removable acrylic dentures. Methods: This is an experimental study with a post test only control group design. Acrylic resin were soaked in treatment extract of 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90%, 100% concentration,0.2% chlorhexidine gluconate and 70% ethanol as the control. One Way ANOVA test and Bonferroni Post Hoc test with 95% confidence level were used. Results: The result of the study shows that the MIC value of 40%, 45%, 50%, 60%, 70%, 80% 90% and 100% of treatment extract were respectively 13:07%; 18:36%; 23.67%; 28.87%; 36.84%; 42.10%; 49.98%; 52.61%. Conclusion: This study concluded that the treatment extract can reduce the amount of Candida albicans,100% concentration made the strongets antifungal effect compared to lesser concentrations and 0.2% chlorhexidine gluconate.Key words: Candida albicans, chlorhexidine gluconate, denture stomatitis, heat cured acrylic resin, MIC, white ginger.